The Effectiveness of Extracurricular Activities in Building Student Character at SMPI Al-Istiqomah Prabumulih - Sheilda Nurgenti; Muharudin Muharudin; Edy Suryana; Randika Pratama (Penerbit Presisi Pustaka, 2026)
This research aims to examine the role of extracurricular activities at SMPI Al-Istiqomah Prabumulih in shaping students' character. The background for choosing this title is based on the need for knowledge to develop students' character in the modern era, where formal education alone is not enough. The research method used is a case study with observations and interviews with educators to collect data related to the implementation of extracurricular activities. The research results show that activities such as scouting, futsal, and archery are effective in training students' discipline, responsibility, and skills. In conclusion, SMPI Al-Istiqomah has successfully created a holistic educational environment that supports the development of a quality and morally upright young generation.